(untitled) (Research, Society and Development, 2020)
Objective: to promote reflections on the subject of indiscipline, with an approach in the school context. Methodology: This is a descriptive study, of the literature review type, based on searches carried out in the Google Scholar and SciElo databases, conducted without a time filter. Results and discussion: Studies have shown that the subject of indiscipline presents itself as one of the greatest obstacles facing schools in contemporary society, causing great anguish in teachers who no longer know how to deal with the situation. However, in order to face the problem, it is necessary to understand what is happening with the discipline today at school: lack of limit for students, lack of interest in doing activities and disrespect for the teacher, as well as the role of the teacher in this process. The vast majority of parents spend all day working in the struggle for survival and the little time they have at home with the family is used by television programs that prevent communication between members, impairing the good relationship of the family. In view of this, undisciplinary problems arise and emerge in the various spheres of social life, including school. Final Considerations: What remains for us is to dream that these theoretical debates about indiscipline will be used effectively in practice and will bear fruit in overcoming these current perspectives. It will be a great job since it deals with something culturally rooted, but it is not impossible.